2006
DOI: 10.1086/505652
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of Large Equivalent Width Lyα Emission in Luminous Lyman Break Galaxies at z ~ 5-6?

Abstract: We report a deficiency of luminous Lyman break galaxies (LBGs) with a large rest-frame equivalent width (EW rest ) of Lya emission at . Combining our spectroscopic sample of LBGs at and those from the z ∼ 5-6 z ∼ 5 literature, we found that luminous LBGs at generally show weak Lya emissions, while faint LBGs show z ∼ 5-6 a wide range of Lya EW rest and tend to have strong ( ) Lya emissions; i.e., there is a deficiencẙ EW տ 20 A rest of strong Lya emission in luminous LBGs. There seems to be a threshold UV lumi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

43
121
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(167 citation statements)
references
References 43 publications
43
121
3
Order By: Relevance
“…Within the options discussed in this paper, this choice best describes the trend of increasing strength of Lyα with redshift as observed from spectroscopic surveys (e.g. Ando et al 2006;Ouchi et al 2008;Stark et al 2010), other studies (Blanc et al 2011;Hayes et al 2011), and our models that allow for varying Lyα strength ).…”
Section: Evolution Of the Physical Properties From Z ∼ 3 To Z ∼mentioning
confidence: 99%
“…Within the options discussed in this paper, this choice best describes the trend of increasing strength of Lyα with redshift as observed from spectroscopic surveys (e.g. Ando et al 2006;Ouchi et al 2008;Stark et al 2010), other studies (Blanc et al 2011;Hayes et al 2011), and our models that allow for varying Lyα strength ).…”
Section: Evolution Of the Physical Properties From Z ∼ 3 To Z ∼mentioning
confidence: 99%
“…With the aim of understanding the different parameters governing the Lyα escape and observability, many studies, both observational and theoretical, have found an apparent variation of the Lyα strength with the UV luminosity (Shapley et al 2003;Ando et al 2006;Ouchi et al 2008;Verhamme et al 2008;Vanzella et al 2009;Pentericci et al 2009;Balestra et al 2010;Stark et al 2010;Schaerer et al 2011;Shimizu et al 2011). In particular, the data show a lack of high Lyα equivalent width in luminous LBGs.…”
Section: Lyα Equivalent Width As a Function Of Uv Luminositymentioning
confidence: 99%
“…Some studies have reported the inverse relationship between Lyα EW and UV luminosity (e.g., Shapley et al 2003;Ando et al 2006;Reddy et al 2008;Stark et al 2010), while others claimed that the relation is not obvious or there is no such relation (e.g., Nilsson et al 2009). Figure 3 shows the Lyα EW as a function of the continuum luminosity M 1300 for our sample.…”
Section: Spectral Propertiesmentioning
confidence: 99%